Physiological performance of Genipa americana L. seeds primed with silicon under salt stress - Joseane Santos da Silva; Martielly Santana dos Santos; Rafael Marani Barbosa (Journal of Seed Science)
ABSTRACT: The physiological priming of seeds from native forest tree species is a promising strategy to face adverse environments. Silicon priming has shown improvements in seed coat, in addition to favoring tolerance to abiotic stresses. The aim of this work was to evaluate the physiological performance of G. americana (G. americana) seeds primed with silicon and subjected to salt stress. Two trials were carried out: in the first one, four lots of seeds were characterized and subsequently primed with silicon doses (0 mM, 2 mM, 10 mM, 60 mM), and water content and physiological performance were evaluated. In the second trial, seeds from the best lot of trial I were primed at the same doses as in the first trial and subjected to salt stress with NaCl, at osmotic potentials of -0.3; -0.6; -0.9; and -1.2 MPa (2.5; 5.0, 7.5; 10.0 dS.m־¹, respectively). For both trials, the following were evaluated: germination, first count, speed index and median germination time, in addition to seedling emergence in a greenhouse. G. americana seeds primed with distilled water and silicon are able to tolerate NaCl-induced stress, with osmotic potentials of up to -0.6 MPa. In the greenhouse, the highest seedling formation rates were observed at an osmotic potential of -0.3 MPa, while above -0.6 MPa there was a reduction in seedling emergence. Si has potential to condition G. americana seeds, improving their physiological quality and generating vigorous seedlings, suitable for reforestation in low quality soils, promoting ecological sustainability and the rational use of degraded areas.